Influence of asthma status on sleep variability in overweight/obese youth. (21st April 2017) - Krietsch, Kendra N.; Lawless, Casey; Fedele, David A.; McCrae, Christina S.; Janicke, David M.
ABSTRACT: Objective : Pediatric asthma and overweight/obesity (OV/OB) frequently co-occur and youth with both conditions exhibit poor sleep/bedtime habits. This study assessed differences in week-to-weekend bedtime/wake time variability among OV/OB youth with/without comorbid asthma, and tested whether variability predicted weekday sleep. Methods : OV/OB youth ( n = 142; 28% comorbid asthma; 7–12 years) wore an Accelerometer for 5 days (2 weekend days), providing estimates of week-to-weekend bedtime/wake-time variability, weekday Total Sleep Time (TST), weekday time in bed (TIB), and weekday wake after sleep onset (WASO). Results : There were no demographic differences between groups beyond lower family income for the OV/OB+asthma group. The OV/OB+asthma group exhibited later weekday (mean OV/OB+asthma = 10:39 pm, mean OV/OB only = 10:30pm) and weekend (mean OV/OB+asthma = 11:41 pm, mean OV/OB only = 11:17pm) bedtimes, earlier weekday waketimes (mean OV/OB+asthma = 6:40 am, mean OV/OB only = 6:51 am), and similar weekend waketimes (mean OV/OB+asthma = 7:54 pm, mean OV/OB only = 7:52 pm. Univariate MANOVA follow-ups indicated a main effect of asthma group for week-to-weekend bedtime and waketime variability, with the OV/OB+asthma group evidencing approximately 30 minutes greater bedtime (OV/OB+asthma mean = 90 minutes) and waketime (OV/OB+asthma mean = 108 minutes) variability. Within the OV/OB+asthma group, greater waketime variability predicted fewer minutes of weekday TIB and WASO. Within the OV/OB only group, wake time variability predicted fewer minutes of weekday TIB. Conclusion : Findings suggest that asthma status confers risk for more week-to-weekend variability among currently OV/OB youth, and that greater variability shortens the weekday sleep period. Further research on reasons for greater week-to-weekend sleep variability in asthma is needed.